Epistemicide on the Record: Theorizing Commemorative Injustice and Reimagining Interdisciplinary Discourses in Cultural Information Studies. Issue 1 (14th October 2022) - Youngman, Tyler; Modrow, Sebastian; Smith, Melissa; Patin, Beth
ABSTRACT: Epistemicide refers to knowledge destruction and is perpetuated through epistemic injustices, which are the ways we harm knowers in the process of their epistemological development. Within acts of commemoration, epistemic injustices can influence the prioritization and politicization of memory, thus shaping our shared understandings of cultural heritage. This paper situates epistemicide within discussions of cultural heritage and collective memory by drawing from existing literature on archival silences. This framing allows us to articulate and define commemorative injustices– memorial injustice, performative injustice, and documentary injustice– expanding the previously established epistemicide framework. Naming commemorative injustices promotes the development of a meta‐language to connect related concepts of knowledge destruction, silencing, and absence across disciplines in cultural information studies. While commemorative injustices are not necessarily committed out of individual mal intent, this paper notes that they are byproducts of culturally constructed historical precedents and social norms. Beyond a theoretical expansion, we explore the designation of evidence of cultural heritage as manifestations of information, name enforced archival silences as instances of commemorative injustice, identify how multiple epistemic injustices may act concurrently to inflict harm, and provide critical theory to inform interventions by drawing on examples of epistemic injustice inflicted by U.S. cultural heritage institutions.